Using Empirical Performance Data to Source Bluebunch and Snake River Wheatgrass Plant Materials to Restoration Sites in the Eastern Great Basin, USA - Thomas A. Jones; Thomas A. Monaco (Ecology and Evolution)
ABSTRACT To infer adaptation of plant material, restoration practitioners often consider only surrogate geographic or climatic information. However, empirical biomass data could assist in deciding what material to use where. To test this approach, we transplanted seven bluebunch wheatgrass (BBWG; Pseudoroegneria spicata) and five Snake River wheatgrass (SRWG; Elymus wawawaiensis) populations to three sites ranging from low to high precipitation (LPPT, MPPT, and HPPT). We measured establishment‐year (2011) biomass at all sites and 2012–16 biomass at MPPT and HPPT. When data were standardized by site, P‐7 and Anatone produced the most BBWG biomass across sites and Wahluke the least in both 2011 and 2012–16, while E‐58X produced the most SRWG biomass and Secar and E‐49X the least in 2011 and 2012–16, respectively. Among BBWG populations in 2011, relative performance of P‐7 (G6 generation) and Goldar increased and Whitmar decreased at wetter sites, while Columbia was stable (high) and Wahluke was stable (low) over sites. Among SRWG populations in 2011, Secar, Secar78, and E‐58X increased at drier sites and Discovery at wetter sites. However, once established, populations of both species were much more similar for trend. In 2012–16, trend somewhat increased for five BBWG populations from MPPT to HPPT, was stable for Wahluke, but declined for Columbia, while all five SRWG populations declined at HPPT. These results suggest that, once established, BBWG is mostly stable across sites, while SRWG is less adapted to wetter sites. In 2012–16, BBWG populations originating at drier (or wetter) sites mostly performed relatively better at MPPT (or HPPT), suggesting adaptation to site. However, in the establishment year (2011), this relationship did not hold, suggesting seedling vigor and immature growth rate play a stronger role than precipitation at the site of origin.